The distribution of radiotoxic 137Cs concentrations in seaweed and mussel species in the Mediterranean Sea - Abbasi, Akbar; Almousa, Nouf; Zakaly, Hesham M. H. (Pergamon-Elsevier Science Ltd, 2023)
A study was conducted to determine the 137Cs activity concentrations in various seaweed and mussel samples from the North East Mediterranean Sea, including the brown algae (Dictyota dichotoma) and oarweed (Laminaria digitata), and mussel species (Haliotis asinina, Mytilus edulis and Mytilus galloprovinciali). The 137Cs activity con-centration in seaweed species exhibited varying levels, ranging from 84.20 +/- 1.82 to 236.05 +/- 5.72 mBq kg-1 fresh weight (fw) for oarweed, and 106.29 +/- 2.26 to 252.38 +/- 6.04 mBq kg -1 fw for brown algae. The 137Cs value in mussel species were between 12.94 +/- 0.51-101.84 +/- 1.35 mBq kg -1 fw for M. galloprovincialis, 15.49 +/- 0.58-71.52 +/- 1.16 mBq kg-1 fw for M. edulis, and 10.36 +/- 0.11-69.13 +/- 1.34 mBq kg -1 fw for H. asinine. When comparing the 137Cs concentration in seaweed and mussel species, the average concentration in seaweeds was approximately four times higher than that in mussels. This significant difference in radioisotope concentration highlights the potential for higher bioaccumulation of 137Cs in seaweeds compared to mussels.
Keywords: Radiotoxic 137 Cs; Mediterranean Sea; Seaweed species; Mussel species; Pollution